2009
DOI: 10.1080/17451000802626547
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive isolation between two sympatric simultaneous hermaphroditic shrimp,Lysmata wurdemanniandL. boggessi

Abstract: To investigate pre-and post-zygotic isolation between two sympatric and phylogenetically related species of Lysmata shrimp, two assays were conducted in the laboratory: (1) no specific mate choice where mating between the two species was 'forced'; (2) specific mate choice or preference where a female had a choice between conspecific and heterospecifc males. Behavioural studies reveal that female L. wurdemanni accepted only conspecific male shrimp, whereas L. boggessi females would mate with an interspecific ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The design of the behavioral assay [23] was to test the bioactivity of the hexane-extractable cuticular compounds. To ensure the test animals were receptive to potential sex pheromones, only MP shrimp were used and no individual was used more than once to avoid potential habituation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the behavioral assay [23] was to test the bioactivity of the hexane-extractable cuticular compounds. To ensure the test animals were receptive to potential sex pheromones, only MP shrimp were used and no individual was used more than once to avoid potential habituation.…”
Section: Methodsmentioning
confidence: 99%
“…We use recent behavioral evidence that suggests the existence of both distance and sparingly water-soluble contact pheromones in Lysmata wurdemanni and L. boggessi [22], [23] to examine the chemical identity of the contact pheromone. The reproductive system of Lysmata species is rare among decapod crustaceans [24]: a shrimp first matures as a male (male phase - MP), but with growth may change into a euhermaphrodite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species are protandric simultaneous hermaphrodites in which juveniles mature as males (male phase) and later become simultaneous hermaphrodites that resemble and function as females (female phase) but have male function; we will refer to these two phases simply as MP and FP, respectively. Zhang et al (2009) and Zhu et al (2012a) found that reproductive isolation of the two species are due to differences in the molecular composition of sex pheromones leading to asymmetric mate recognition. MP L. boggessi rarely mate with FP L. wurdemanni because males cannot recognize the soluble sex pheromones from those FPs.…”
Section: Recognition Of Conspecificsmentioning
confidence: 99%
“…Further research with two species of Lysmata shrimp, which are protandric simultaneous hermaphrodites, tested the factors that might contribute to conspecific selection during mating. 184 Behavioral experiments showed that conspecifics would always mate, but male L. boggessi would not mate with female L. wurdemanni. However, female L. boggessi would copulate with male L. wurdemanni if no L. boggessi males were present, and this interspecific mating was more frequent when the shrimp were held in the dark.…”
Section: Crustaceansmentioning
confidence: 99%